Monitoring LITT thermal penetration depth using real‐time analysis of backscattered light. Issue 6 (28th November 2012) - Shacham, Ranit; Steinberg, Idan; Gandjbakhche, Amir H.; Gannot, Israel
Abstract Real‐time monitoring of the thermal penetration depth (TPD) is essential in various clinical procedures, such as Laser Interstitial Thermal Therapy (LITT). MRI is commonly used to this end, though bulky and expensive. In this paper, we present an alternative novel method for an optical feedback system based on changes in the diffused reflection from the tissue during treatment. Monte‐Carlo simulation was used to deduce the relations between the backscattered pattern and the TPD. Several methods of image analysis are developed for TPD estimation. Each yields a set of parameters which are linearly dependent on the TPD. In order to test these experimentally, tissue samples were monitored in‐vitro during treatment at multiple wavelengths. The SNR and coefficient of determination were used to compare the various methods and wavelengths and to determine the preferred method. Such system and algorithms may be used for real‐time in‐vivo control during laser thermotherapy and other clinical procedures. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)